'Bottom dog men': Disability, Social Welfare and Advocacy in the Scottish Coalfields in the Interwar Years, 1918–1939. (September 2017) - Turner, Angela; McIvor, Arthur
Abstract : This article connects with and builds on recent research on workmen's compensation and disability focussing on the Scottish coalfields between the wars. It draws upon a range of primary sources including coal company accident books, court cases and trade union records to analyse efforts to define and redefine disability, examining the language deployed and the agency of workers and their advocates. It is argued here that the workmen's compensation system associated disability with restricted functionality relating to work tasks and work environments. Disability became more visible and more closely monitored and this was a notably contested and adversarial terrain in Scotland in the Depression, where employers, workers and their collective organisations increasingly deployed medical expertise to support their cases regarding working and disabled bodies. In Scotland, the miners' trade unions emerged as key advocates for the disabled.